An Analysis of English Textbooks “My Next Words” for the Fourth Grade - Lia Aprilia; Evi Karlina Ambarwati (Universitas Pendidikan Mandalika, 2023)
Textbooks are one of the most important media which facilitate the learning process because they can support students in developing students thinking skills. The use of English textbooks in the classroom aims to assist teachers in achieving learning objectives. This research aims to determine the feasibility of the English textbook My Next Words based on the criteria developed by Badan Standar Nasional Pendidikan or National Education Standards Agency. The design used in this study is descriptive qualitative. Then, the fourth-grade textbook My Next Words became a document that would be used as an object of study. The technique for collecting data in this study is a literature study and the instrument used in this study is a checklist of criteria based on standard criteria from BSNP. Based on the results of the evaluation that has been carried out, the results of the analysis show that the My Next Words book is appropriate from all aspects based on the framework of the BSNP for the evaluation of textbooks. The feasibility test of this book is carried out to ensure that the book to be used by students has presented material that is in accordance with the level of student development, does not contain pornography, racism, deviations, uses clear and straightforward language, and readability of writing that can be read by students. Although the book has met various aspects of the assessment, there are still some parts that need to be improved, such as the quality of the book, the accuracy of the material, and other learning support activities.